Adaptive Code with Non-Uniform Modulation on OFDM Subcarriers Modeling for Underwater Acoustic Environment - Wulandari, Sholihah Ayu; Santoso, Tri Budi; Astawa, I Gede Puja (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
In this paper, an Adaptive Code NonUniform Modulation with Orthogonal Frequency Division Multiplexing (OFDM) System was evaluated in the underwater acoustic communication channel. This system was adopted from the Subcarrier arrangement of the OFDM standard of IEEE 802.11a, and improved with some modifications. There are three schemes in the proposed adaptive system. The first is the Hamming code with Binary phase-shift keying (BPSK) modulated, which is mapped for 12-bit subcarrier data. The second is the Bose-Chaudhuri-Hocquenghem (BCH) code with Quadrature phase-shift keying (QPSK) modulation which is for the other 12-bit subcarrier data. And the third is the Reed Solomon code with 16-Quadrature Amplitude Modulation (16- QAM) modulation that is mapped for 24-bit subcarrier data. The system modeling was evaluated in the shallow water acoustic environments. Bit error rate (BER) and signal-to-noise ratio (SNR) were analyzed to evaluate the proposed system performance. The evaluation results showed that the proposed system was able to improve the performance better than the fixed modulation or un-coded Non-uniform modulation. At the same bit error limit which is 0.001, BPSK, QPSK, 16-QAM, uncoded Non-uniform modulation, and the proposed system have its own SNR, i.e.; 24.9 dB, 8.5 dB, 10.3 dB, 7 dB, and 2 dB, respectively. The proposed system requires lower power to achieve an error rate of 0.001. In addition, between the proposed system and un-coded Non-uniform modulation, it has a coding gain of 5dB.